Progress of plasma rotating electrode processing technology - TANG Huiping (Fenmo yejin jishu)
Plasma rotating electrode process (PREP) is one of the key technologies for producing high quality spherical metal powders. The liquid film is thrown out to form the droplets by the centrifugal force generated by the high-speed rotation of the electrode, which will atomize and solidify into the spherical powders in an inert atmosphere. The metal powders prepared by PREP have become the important raw materials for additive manufacturing, hot isostatic pressing, surface spraying, and other manufacturing technologies. The history and current status of PREP technology at home and abroad were reviewed in this paper, and the development situation of the PREP equipment and technology in China was summarized. Finally, the development trends and the main scientific issues were pointed out for the further research.